AN ANALYSIS OF DEIXIS USED BY STEVE HARVEY’S ON YOUTUBE CHANNEL - Susi Era Veri Lumban Gaol; Fenty Debora Napitupulu; Harpen Silitonga; Bangun Munthe (Sean Institute, 2023)
This research deals with an analysis of deixis used by Steve Harvey on YouTube channels based on Yule’s theory. The objectives of this research are to identify the types of deixis used by Steve and the guest on Steve’s TV Show on the YouTube channel video and to identify how the use of deixis affects the meaning of the whole utterances of Steve and the guest. The data of this research is the utterance of Steve and the guest that contains Deixis. In this research, the writer analyzed the deixis found in the videos